Level of Knowledge of Adolescent Girls of Madrasah Aliyah Pesantren Islam Al-Mukmin Ngruki Sukoharjo on Bullying Behavior - Irma Dwi Kusmiasari; Wikan Basworo; Martiana Sucingtyas Tri Artanti; Dewanto Yusuf Priyambodo; Ida Bagus Gede Surya Putra Pidada; Adam Juan Poga (Lambung Mangkurat University, 2024)
Bullying is an aggressive behavior carried out intentionally and repeatedly, causing the victim to feel hurt and oppressed. This phenomenon is still prevalent among Indonesian adolescents, including in Islamic boarding schools, which are supposed to be centers for instilling Islamic values. This study aimed to describe the level of knowledge about bullying among female students at Madrasah Aliyah (MA) Pondok Pesantren Islam Al-Mukmin Ngruki Sukoharjo. The research utilized a descriptive quantitative method, targeting female students in grade XI. A total of 129 respondents were involved using total sampling, and data were collected through questionnaires and analyzed descriptively. The results revealed that most female students had a good level of knowledge. Based on majors, the highest knowledge level was found among students in religious studies (98.3%), while based on region, students from outside Solo dominated the good category (97.1%). Raising awareness about bullying can be done through early education that includes its definition, types, effects, and ways to prevent it. These findings can also serve as baseline data for comparing bullying levels among male and female adolescent.